Correlation Between Membranectomy in Chronic Subdural Hematoma and Postoperative Seizures: A Retrospective Institution-Based Analysis at a Tertiary Care Center in India - Kundu, Palash; Choudhary, Ram K.; Jaluka, Dinesh; Pal, Barun K.; Dhal, Amar C. (International Journal of Epilepsy, 2025)
Chronic subdural hematoma (SDH) is a common neurosurgical condition, particularly in the elderly, characterized by blood accumulation between the dura and arachnoid membranes. While burr-hole drainage remains the standard treatment, some surgeons perform membranectomy—surgical removal of the hematoma's encapsulating membranes—believing it reduces recurrence and facilitates brain re-expansion. However, its role in influencing postoperative complications, especially seizures, remains controversial.This study aimed to assess the correlation between membranectomy and the incidence of postoperative seizures in patients surgically treated for chronic SDH, and to compare these findings with existing literature to guide clinical decision-makingHospital-based retrospective analytical study.A retrospective analytical study was conducted at R.G. Kar Medical College, Kolkata, including 56 patients treated surgically for chronic SDH between November 2024 and April 2025. Data on demographics, comorbidities, radiological characteristics, surgical procedures (with or without membranectomy), and postoperative outcomes were collected. All patients received prophylactic antiseizure medications. The incidence of postoperative seizures was analyzed, and statistical significance was tested using chi-square analysis with odds ratios.Of the 56 patients, 22 underwent membranectomy with their primary procedure, while 34 did not. Overall, 14.3% developed postoperative seizures despite prophylaxis. The seizure rate was 27.3% in the membranectomy group, compared with 5.9% in the non-membranectomy group. The odds ratio for developing seizures with membranectomy was 6 (95% confidence interval: 1.09–33.2; p = 0.0025), indicating a statistically significant association.This institutional study demonstrates that membranectomy in chronic SDH surgery is associated with a significantly higher risk of postoperative seizures, aligning with some previous reports. Given the increased morbidity associated with seizures, routine membranectomy should be reconsidered, emphasizing burr-hole drainage as the primary approach unless otherwise clinically indicated. Further large-scale studies are warranted to validate these findings and optimize surgical protocols for chronic SDH.
Keywords: chronic subdural hematoma; seizure; membranectomy